Predicting Marital Satisfaction Based on Worry Domains and Psychosocial Adjustment in Female Diabetic Patients - Adeleh Emamjomeh; Ali Reza Manzari Tavakoli; Hamid Molayi Zarandi (Iranian Journal of Educational Research)
Objective: The purpose of this research is to examine a predicting model of marital satisfaction based on worry domains and psychosocial adjustment in female diabetic patients (referred to specialized diabetes clinics in Tehran) in 2023. Methods: The current research is a correlational design based on structural equation modeling. The statistical population included all married people with type 2 diabetes (age range 30 to 55 years) referring to specialized diabetes clinics in Tehran in the summer and fall of 2023, which are 2143 people. The sample included 412 married female patients who were selected by systematic random sampling. The research tools of The Worry Domains Questionnaire (WDQ) (Tallis et al., 1992), The Psychosocial Adjustment Scale (Derogatis & Derogatis, 1990), and Nathan H.'s Marital Satisfaction Questionnaire. In order to analyze the hypotheses, the structural equation method via AMOS software was used. Results: Results showed a significant negative relationship between the worry domains and marital satisfaction and a significant positive relationship between psychosocial adjustment and marital satisfaction. According to the findings, the proposed model has good fit indices. Also, according to the findings, 23 and 38 percent of changes in marital satisfaction are explained by worry domains and psychosocial adjustment, respectively. Conclusion: The findings support the role of psychosocial adjustment in improving marital satisfaction and the reducing effect of worry domains on marital satisfaction.